ChemInform Abstract: Novel 3‐D Nanoporous Graphitic‐C3N4 Nanosheets with Heterostructured Modification for Efficient Visible‐Light Photocatalytic Hydrogen Production. Issue 7 (29th January 2015) - Yuan, Jielin; Gao, Qiongzhi; Li, Xin; Liu, Yingju; Fang, Yueping; Yang, Siyuan; Peng, Feng; Zhou, Xiaosong
Abstract Phosphorus‐doped graphitic‐C3N4 nanosheets coupled with BiPO4 nanorods are hydrothermally synthesized from aqueous solutions containing CH2N2, NaH2PO4, Bi(NO3)3, and HNO3 (autoclave, 483 K, 4 h), followed by calcination at 823 K for 4 h.